Corruption as a Security Threat in Russia and Violation of Conduct of Civil Servants - Viktor Petrovich Kirilenko (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Effective functioning of any economic system from microeconomic to macroeconomic level depends on the quality of the professional activity of the state as an economic entity. In this paper, corruption is regarded as a serious breach of business ethics of civil servant developing into one of the key threats to Russia’s national security.